Rancang Bangun Sistem Prediksi Financial Distress Menggunakan Metode Altman Z-Score Modifikasi Pada Koperasi XYZ - Ni Made Lissa Primadani; Ni Kadek Ariasih (INFORMAL: Informatics Journal, 2021)
Financial distress is a condition in which a company begins to show signs of bankruptcy due to a decline in the company's financial condition. XYZ Cooperative is a savings and loan cooperative that needs to be aware of experiencing financial distress. What's more, the XYZ cooperative has experienced fluctuating asset conditions, even for profit in a certain month, it has experienced a negative or loss condition. Another problem that occurred is the covid-19 pandemic which made it difficult for people to carry out their obligations such as paying credit. This made the XYZ Cooperative's income experience a drastic decline from the previous year. Meanwhile, currently XYZ Cooperative does not have a prediction system or has never predicted financial distress in its company Based on these problems, an idea emerged to design and build a financial distress prediction system at the XYZ Cooperative using the Modified Altman Z-Score method. This model was chosen because the financial ratios used in prediction calculations are in accordance with the financial ratios of the XYZ Cooperative. The final result of this research is the construction of a prediction system using the Altman Z-Score Modification method on the desktop-based XYZ Cooperative. From the 3 years of financial reports that were tested from 2017 to 2019, the prediction results were at a safe point, namely the Z value above 2.6. The calculation results for 2017 is 8.19, 2018 is 8.11 and 2019 is 7.82. However, the predicted Z value from 2017 to 2019 has decreased, although it is not significant. The accuracy calculation obtained compares the prediction results with the real situation of the cooperative using the average comparison formula and the typer error II formula. Where from the 3 sample data tested, the results of the sample received were 3 with a data error of 0.